A comprehensive scenario of orchid nutrition – a review. (6th January 2021) - Biswas, Siddhartha Sankar; Singh, D. R; De, L. C; Kalaivanan, N. S.; Pal, Ram; Janakiram, T.
Abstract: Nutritional requirement of orchids is similar to other plants. Still, being mostly epiphytic, they have special mechanisms by which they can survive in limited nutrient condition without showing any deficiency symptom. Also because of their epiphytic nature, domesticating them as a pot plant is quite challenging. Nutritional management in orchids is more complicated than any other agri-horticultural crops. For orchids, water-soluble nutrients are applied in solution form, at a regular interval at once or twice a week. Unlike other crops, basal application or two to three split application of nutrients are not recommended for orchids. Studies conducted throughout the world show N, P and K play a significant role for successful orchid growing. Most of the orchid nutritional study in the world had considered N, P and K as the key elements of study. There are several reports on the benefit of the integrated application of organic and inorganic nutrients to the orchids.